Anode for alkaline water electrolysis and method for producing same

The use of a lithium composite oxide catalytic layer with a rock salt structure on an alkaline water electrolysis anode addresses the issue of rapid deterioration with renewable energy, providing stable performance and durability.

JP7625204B2Active Publication Date: 2025-02-03KYOTO UNIV +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020129161
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-07-30
Publication Date
2025-02-03
Estimated Expiration
2040-07-30

AI Technical Summary

Technical Problem

Existing alkaline water electrolysis anodes deteriorate quickly when used with renewable energy sources due to high output fluctuations, and current manufacturing methods are complex and impractical.

Method used

A catalytic layer composed of lithium composite oxides with a rock salt structure, containing lithium, nickel, iron, and aluminum, is formed on a conductive base, stabilized by an intermediate layer of nickel oxides, to enhance durability and catalytic activity.

Benefits of technology

The anode maintains excellent catalytic activity and reduces deterioration even with high output fluctuations, ensuring stable performance over a long period.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625204000001
    Figure 0007625204000001
  • Figure 0007625204000002
    Figure 0007625204000002
  • Figure 0007625204000003
    Figure 0007625204000003
Patent Text Reader

Abstract

To provide an alkaline water electrolysis anode in which an excellent catalytic activity is stably maintained for a long period of time with electrolytic performance hardly degraded even when a power source is an electric power having large output fluctuation such as a renewable energy.SOLUTION: An alkaline water electrolysis anode 10 comprises: a conductive substrate 2, at least the surface of which is composed of nickel or a nickel-based alloy; and a catalyst layer 6, which is arranged on the surface of the conductive substrate 2, and which is composed of a lithium complex oxide having a rock salt structure. The lithium complex oxide includes lithium (Li), nickel (Ni), iron (Fe), and aluminum (Al). The atomic ratio of Li / Ni / Fe / Al / O is (0.4-1.1) / (0.4-0.8) / (0.05-0.2) / (0.05-0.2) / 2.0.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an anode for alkaline water electrolysis and a method for producing the same. [Background technology]

[0002] Hydrogen is suitable for storage and transportation, and is a secondary energy with a small environmental impact, so hydrogen energy systems that use hydrogen as an energy carrier are attracting attention. Currently, hydrogen is mainly produced by steam reforming of fossil fuels. However, from the perspective of global warming and the problems of fossil fuel depletion, it is important to produce hydrogen by water electrolysis using renewable energy such as solar power and wind power, among other fundamental technologies. Water electrolysis is low-cost and suitable for large-scale production, making it a promising technology for hydrogen production.

[0003] Among the components used in water electrolysis, the oxygen evolution overvoltage of anode materials under actual operating conditions often exceeds 0.3 V. This means that there is room for significant improvement compared to the overvoltage of around 0.1 V for hydrogen and chlorine evolution currently used in the electrolysis industry. When using electricity with large output fluctuations, such as renewable energy, as the power source for water electrolysis, anodes that can stably maintain excellent catalytic activity over long periods of time are still in the development stage and have not yet been put to practical use.

[0004] Currently, practical water electrolysis can be broadly divided into two types. One is alkaline water electrolysis, in which a highly concentrated alkaline aqueous solution is used as the electrolyte. The other is solid polymer water electrolysis, in which a solid polymer membrane (SPE) is used as the electrolyte. When performing large-scale hydrogen production by water electrolysis, it is said that alkaline water electrolysis, which uses inexpensive materials such as nickel and other iron-based metals, is more suitable than solid polymer water electrolysis, which uses electrodes that use large amounts of expensive precious metals.

[0005] High-concentration alkaline aqueous solutions become more conductive as the temperature rises, but they also become more corrosive. For this reason, the upper limit of the operating temperature is limited to around 80-90°C. With the development of materials for the electrolysis cell and various piping materials that can withstand high temperatures and high-concentration alkaline aqueous solutions, as well as the development of low-resistance diaphragms and electrodes with enlarged surface areas and catalysts, it has become possible to achieve a current density of 0.6 Acm. -2 The electrolytic cell voltage in has improved to below 2V.

[0006] Nickel-based materials that are stable in highly concentrated alkaline aqueous solutions are used as anodes for alkaline water electrolysis, and it has been reported that nickel-based anodes have a lifespan of several decades or more in the case of alkaline water electrolysis using a stable power source (Non-Patent Documents 1 and 2). However, when renewable energy is used as the power source, harsh conditions such as frequent start-stops and load fluctuations are often encountered, and performance degradation of nickel-based anodes is an issue (Non-Patent Document 3).

[0007] Both the nickel oxide production reaction and the reduction reaction of the produced nickel oxide proceed on the metal surface. Therefore, these reactions promote the detachment of the electrode catalyst formed on the metal surface. When the power supply for electrolysis is stopped, the electrolysis stops and the nickel-based anode is maintained at a potential lower than the oxygen evolution potential (1.23 V vs. RHE) and higher than the counter electrode, the cathode for hydrogen generation (0.00 V vs. RHE). In the electrolysis cell, electromotive forces are generated by various chemical species, and the anode potential is maintained low as the cell reaction proceeds, promoting the reduction reaction of nickel oxide.

[0008] In the case of an electrolysis stack in which a plurality of cells, such as an anode chamber and a cathode chamber, are combined, the current generated by the cell reaction leaks through the piping connecting the cells. As a measure to prevent such current leakage, for example, there is a method of continuing to flow a small current when the operation is stopped. However, in order to continue to flow a small current when the operation is stopped, special power supply control is required, and oxygen and hydrogen are constantly generated, which results in excessive effort in operation and management. In addition, in order to intentionally avoid a reverse current state, it is possible to prevent the cell reaction by draining the electrolyte immediately after stopping, but this is not considered to be an appropriate measure when operation with electricity with large output fluctuations such as renewable energy is assumed.

[0009] Conventionally, platinum group metals, platinum group metal oxides, valve metal oxides, iron group oxides, lanthanide group metal oxides, etc. have been used as catalysts (anode catalysts) for oxygen generation anodes used in alkaline water electrolysis. Other anode catalysts include nickel-based alloys such as Ni-Co and Ni-Fe; nickel with expanded surface area; spinel-based Co 3 O 4 , NiCo 2 O 4 , the perovskite-based LaCoO 3 , LaNiO 3 Conductive oxides (ceramic materials) such as those mentioned above; oxides of precious metals; and oxides of lanthanide metals and precious metals are also known (Non-Patent Document 3).

[0010] In recent years, as oxygen-generating anodes used in high-concentration alkaline water electrolysis, there have been proposed an anode for alkaline water electrolysis in which a lithium-containing nickel oxide catalyst layer containing lithium and nickel at a predetermined molar ratio is formed on the surface of a nickel substrate (Patent Document 1), and an anode for alkaline water electrolysis in which a catalyst layer containing a nickel-cobalt oxide and an iridium oxide or a ruthenium oxide is formed on the surface of a nickel substrate (Patent Document 2).

[0011] By the way, layered rock salt LiNiO 2 The oxygen gas overvoltage of the catalyst decreased with the addition of Li.0.5 Ni 0.5 It has been reported that the activity is highest when the catalyst is represented by a layer structure, Ni 3+ The specific electronic structure resulting from the generation of LiO and high electronic conductivity is used to design highly active and durable catalytic materials. + By doping, the Li mobility, local structure, and electronic state of the active site (Ni) are adjusted, and Ni is mixed into the 3a site of Li, and Li + It is possible to suppress dissolution through the diffusion path, and the composition is Li 0.5 Ni 0.5 It is believed that high oxygen evolution activity is maintained when the oxygen-evolving activity is expressed as O (Figure 2).

[0012] The amount of cations mixed between the 3a and 3b sites can be controlled by adjusting the heat treatment conditions in air or oxygen. From the results of Rietveld analysis and ICP, it has been found that the lattice constant changes in proportion to the amount of Li according to Vegard's law. It is also known that samples with the largest amount of mixed cations show high durability in oxygen generation tests in KOH solutions. The catalyst deterioration is thought to be caused by the desorption of Li from the crystals, and it can be suppressed by increasing the amount of mixed cations. Operando XAFS measurements during the electrolysis reaction have also revealed that the basic crystal structure, Li x NiO 2 It is known that the layered salt structure of is maintained even after Li is removed. Material design that prevents the dissolution of Li into the electrolyte is important for utilizing Li-containing metal oxides.

[0013] In addition, LiNi 0.8 Al 0.2 O 2 It has been reported that LiNiO exhibits high oxygen evolution activity (Non-Patent Document 5). It is speculated that Al plays a role in stabilizing the structure during polarization due to a synergistic effect with Ni. A layered rock salt structure has been developed by heat treatment in oxygen gas. 2 Ni layer 3+ Stabilize Li + Ni layer2+ In order to suppress the mixing of Al 3+ In addition, we are focusing on doping LiNi 0.8 Fe 0.2 O 2 It has been reported that it exhibits high oxygen generating activity (Non-Patent Document 6).

[0014] Also proposed is a method for producing an anode for electrolysis of water in which a nanosheet material containing NiFe hydroxide and Ce oxide is formed on nickel foam (Patent Document 3), and a method for producing an anode in which a nanosheet material containing NiFe hydroxide, Co, Mo, and P is formed on nickel foam (Patent Document 4). It has also been disclosed that a material in which NiFe hydroxide is formed on nickel foam can be applied to sensors for ampicillin, nitrate ions, or tetracycline antibiotics (Patent Documents 5 and 6). [Prior art documents] [Patent documents]

[0015] [Patent Document 1] JP 2015-86420 A [Patent Document 2] JP 2017-190476 A [Patent Document 3] China Patent Publication No. 108447703 [Patent Document 4] China Patent Application Publication No. 110344078 [Patent Document 5] China Patent Application Publication No. 109254049 [Patent Document 6] China Patent Application Publication No. 108107101 [Non-patent literature]

[0016] [Non-Patent Document 1] PWTLu, S.Srinivasan, J.Electrochem.Soc.,125, 1416 (1978) [Non-Patent Document 2] CT Bowen, Int.J.Hydrogen Energy,9,59 (1984) [Non-Patent Document 3] S. Mitsushima et al., Electrocatalysis, 8, 422 (2017) [Non-Patent Document 4] Fu, G.; Wen, X.; Xi, S.; Chen, Z.; Li, W.; Zhang, J.; Anton, T.; Wu, R. Qi, D.; Du, Y.; Cheng, J.; Kelvin, HLZ Tuning the Electronic Structure of NiO via Li Doping for the Fast Oxygen Evolution Reaction. Chem Mater, 2019, 31, 419-428 [Non-Patent Document 5] Gupta, A.; Chemelewski, WD; Buddie Mullins, C.; Goodenough, JB, High-rate oxygen evolution reaction on Al-doped LiNiO2. Adv Mater 2015, 27 (39), 6063-7 [Non-Patent Document 6] Zhu, K.; Wu, T.; Zhu, Y.; Li, X.; Li, M.; Lu, R.; Wang, J.; Zhu, X.; Yang, W., Layered Fe-Subposed LiNiO2 Electrocatalysts for High-Efficiency Oxygen Evolution Reaction. ACS Energy Letters 2017, 2 (7), 1654-1660 Summary of the Invention [Problem to be solved by the invention]

[0017] However, even the alkaline water electrolysis anodes proposed in Patent Documents 1 and 2 have problems in that when they are powered by electricity with large output fluctuations, such as renewable energy, their performance is easily degraded and it is difficult to use them stably for a long period of time. 0.8 Al 0.2 O 2 and LiNi reported in Non-Patent Document 6. 0.8 Fe 0.2 O 2 However, the activity of these catalysts is not necessarily sufficiently high, and there is room for further improvement. The production methods proposed in Patent Documents 3 and 4 are both complicated and not necessarily practical.

[0018] The present invention has been made in consideration of such problems associated with the conventional techniques, and an object of the present invention is to provide an anode for alkaline water electrolysis that is less likely to deteriorate in electrolysis performance and maintains excellent catalytic activity stably for a long period of time, even when powered by electric power with large output fluctuations, such as renewable energy. Another object of the present invention is to provide a method for producing the anode for alkaline water electrolysis. [Means for solving the problem]

[0019] As a result of intensive research aimed at solving the above problems, the present inventors have discovered a lithium-containing nickel oxide (LiNiO 2 By doping aluminum (Al) and iron (Fe) into Ni, the two elements act synergistically to produce Ni 3+ The present inventors have found that this stabilizes the catalyst and provides a highly active catalyst, and have thus completed the present invention.

[0020] That is, according to the present invention, there is provided an anode for alkaline water electrolysis as described below. [1] An anode for alkaline water electrolysis comprising: a conductive substrate, at least a surface of which is made of nickel or a nickel-based alloy; and a catalytic layer arranged on the surface of the conductive substrate and made of a lithium composite oxide having a rock salt structure, wherein the lithium composite oxide contains lithium (Li), nickel (Ni), iron (Fe), and aluminum (Al), and the atomic ratio of Li / Ni / Fe / Al / O is (0.4-1.1) / (0.4-0.8) / (0.05-0.2) / (0.05-0.2) / 2.0. [2] The diffraction peak intensity I of the 104 plane of the catalyst layer measured by X-ray diffraction (104) Diffraction peak intensity I of the 003 plane (003) The ratio (I (003) / I (104) ) is 0.1 to 1.9. [3] A compound having the formula Li disposed between the conductive substrate and the catalyst layer. x Ni 2-x O 2 The anode for alkaline water electrolysis according to [1] or [2], further comprising an intermediate layer made of a lithium-containing nickel oxide represented by (0.02≦x≦0.5).

[0021] Furthermore, according to the present invention, there is provided the following method for producing an anode for alkaline water electrolysis. [4] A method for producing an anode for alkaline water electrolysis, comprising: applying an aqueous precursor solution containing a lithium component, a nickel component, an iron component, and an aluminum component to a surface of a conductive substrate, at least the surface of which is made of nickel or a nickel-based alloy; and heat-treating the conductive substrate to which the aqueous precursor solution has been applied at 400 to 800°C in an oxygen-containing atmosphere to form a catalyst layer made of a lithium composite oxide having a rock salt structure on the surface of the conductive substrate, wherein the lithium composite oxide contains lithium (Li), nickel (Ni), iron (Fe), and aluminum (Al) and the atomic ratio of Li / Ni / Fe / Al / O is (0.4 to 1.1) / (0.4 to 0.8) / (0.05 to 0.2) / (0.05 to 0.2) / 2.0. [5] The method for producing an anode for alkaline water electrolysis according to [4], wherein the conductive substrate coated with the aqueous precursor solution is heat-treated in an oxygen-containing atmosphere having an oxygen partial pressure of 0.5 atmospheres or more. Effect of the Invention

[0022] The present invention can provide an anode for alkaline water electrolysis that is less likely to deteriorate in electrolysis performance and maintains excellent catalytic activity stably for a long period of time even when powered by renewable energy or other electric power with large output fluctuations. The present invention also can provide a method for producing the anode for alkaline water electrolysis. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is a cross-sectional view illustrating a schematic diagram of one embodiment of an anode for alkaline water electrolysis according to the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing the state of an oxygen generating anode used in an alkaline water electrolysis method. [Diagram 3] FIG. 1 shows an X-ray diffraction pattern of LiNiO2 having a layered rock-salt structure. [Figure 4] FIG. 1 shows an X-ray diffraction pattern of Li(Ni0.8Fe0.2)0.9Al0.1O2 having a layered rock-salt structure. [Diagram 5] FIG. 1 is a diagram showing the results of cyclic voltammetry measurements (cyclic voltammograms).

[0024] <Anode for alkaline water electrolysis> Fig. 1 is a cross-sectional view that illustrates a schematic diagram of one embodiment of the anode for alkaline water electrolysis of the present invention. As shown in Fig. 1, the anode 10 for alkaline water electrolysis of this embodiment comprises a conductive substrate 2, an intermediate layer 4 formed on the surface of the conductive substrate 2, and a catalyst layer 6 formed on the surface of the intermediate layer 4. The anode for alkaline water electrolysis of the present invention (hereinafter also simply referred to as "anode") is described in detail below.

[0025] (Conductive substrate) The conductive substrate 2 is a conductor for conducting electricity for electrolysis, and is a member having a function as a carrier for supporting the intermediate layer 4 and the catalyst layer 6. At least the surface of the conductive substrate 2 (the surface on which the intermediate layer 4 and the catalyst layer 6 are formed) is made of nickel or a nickel-based alloy. That is, the conductive substrate 2 may be entirely made of nickel or a nickel-based alloy, or only the surface may be made of nickel or a nickel-based alloy. Specifically, the conductive substrate 2 may be a metal material such as iron, stainless steel, aluminum, titanium, etc., on whose surface a coating of nickel or a nickel-based alloy is formed by plating or the like.

[0026] The thickness of the conductive substrate is preferably 0.05 to 5 mm. The conductive substrate is preferably shaped to have openings for removing bubbles of oxygen, hydrogen, etc. that are generated. For example, an expanded mesh or a porous expanded mesh can be used as the conductive substrate. When the conductive substrate is shaped to have openings, the opening ratio of the conductive substrate is preferably 10 to 95%.

[0027] (Middle class) The anode of the present invention preferably includes an intermediate layer disposed between the conductive substrate and the catalyst layer. As shown in FIG. 1, the intermediate layer 4 is a layer formed on the surface of the conductive substrate 2. The intermediate layer 4 suppresses corrosion of the conductive substrate 2 and stably fixes the catalyst layer 6 to the conductive substrate 2. The intermediate layer 4 also plays a role in quickly supplying a current to the catalyst layer 6. The intermediate layer 4 is a layer having a composition formula of Li x Ni 2-x O 2 It is preferable that the intermediate layer 4 is formed of a lithium-containing nickel oxide represented by the formula (0.02≦x≦0.5). If x in the formula is less than 0.02, the electrical conductivity may be somewhat insufficient. On the other hand, if x exceeds 0.5, the physical strength and chemical stability may be somewhat decreased. The intermediate layer 4 formed of the lithium-containing nickel oxide represented by the formula has sufficient electrical conductivity for electrolysis and exhibits excellent physical strength and chemical stability even when used for a long period of time.

[0028] The thickness of the intermediate layer is preferably 0.01 μm or more and 100 μm or less, and more preferably 0.1 μm or more and 10 μm or less. If the thickness of the intermediate layer is less than 0.01 μm, the above-mentioned functions are not exhibited. On the other hand, if the thickness of the intermediate layer exceeds 100 μm, the voltage loss due to the resistance in the intermediate layer increases, making it difficult to exhibit the above-mentioned functions, and may be somewhat disadvantageous in terms of manufacturing costs, etc.

[0029] (catalyst layer) The catalyst layer 6 is a layer having catalytic activity that is formed on the surface of the intermediate layer 4. By interposing the intermediate layer 4, the catalyst layer 6 is fixed more firmly onto the conductive substrate 2.

[0030] The catalytic layer is formed of a lithium composite oxide having a rock salt structure. This lithium composite oxide contains lithium (Li), nickel (Ni), iron (Fe), and aluminum (Al), and the atomic ratio of Li / Ni / Fe / Al / O is (0.4-1.1) / (0.4-0.8) / (0.05-0.2) / (0.05-0.2) / 2.0. By providing the catalytic layer formed of a lithium composite oxide having a composition in which Li, Ni, Fe, Al, and O are expressed in the above ratio, even when electricity with large output fluctuations such as renewable energy is used as the power source, the electrolytic performance is not easily deteriorated and excellent catalytic activity can be stably maintained for a long period of time.

[0031] The lithium composite oxide constituting the catalyst layer has a layered rock-salt structure. The developed rock-salt structure of the lithium composite oxide makes it more resistant to degradation of electrolytic performance, and excellent catalytic activity is stably maintained. Whether or not the lithium composite oxide constituting the catalyst layer has a rock-salt structure can be confirmed by analyzing the catalyst layer by X-ray diffraction. For example, by X-ray diffraction using Cu-Kα radiation, the diffraction peaks at around 2θ=18° corresponding to the 003 plane of the catalyst layer and at around 2θ=44° corresponding to the 104 plane are measured. The relative intensity ratio (I (003) / I (104)) indicates that the layered rock salt structure is more developed. More specifically, the diffraction peak intensity I (104) Diffraction peak intensity I of the 003 plane (003) The ratio (I (003) / I (104) ) is preferably 0.1 to 1.9, and more preferably 0.2 to 1.8. FIG. 3 shows LiNiO 2 This X-ray diffraction pattern was subjected to Rietveld analysis to obtain the diffraction peak intensity I (104) Diffraction peak intensity I of the 003 plane (003) The ratio (I (003) / I (104) It has been confirmed that the diffraction peak intensity I of the 104 plane is 0.1 to 1.9. When the X-ray diffraction pattern of the lithium composite oxide containing Li, Ni, Fe, and Al used in the anode of this embodiment is subjected to Rietveld analysis, (104) Diffraction peak intensity I of the 003 plane (003) The ratio (I (003) / I (104) ) is in the range of 0.1 to 1.9, and the above LiNiO 2 It has been confirmed that it has a layered rock-salt structure similar to that of

[0032] The thickness of the catalyst layer is preferably 0.01 μm or more and 100 μm or less, and more preferably 0.1 μm or more and 10 μm or less. If the thickness of the catalyst layer is less than 0.01 μm, the above-mentioned functions are not realized. On the other hand, if the thickness of the catalyst layer exceeds 100 μm, the voltage loss due to the resistance in the catalyst layer increases, making it difficult to realize the above-mentioned functions, and may be somewhat disadvantageous in terms of production costs, etc.

[0033] <Method of manufacturing an anode for alkaline water electrolysis> Next, a method for producing an anode for alkaline water electrolysis of the present invention will be described. The method for producing an anode described below is a method for suitably producing the above-mentioned anode for alkaline water electrolysis. The method for producing an anode of the present invention includes a step of applying an aqueous precursor solution containing a lithium component, a nickel component, an iron component, and an aluminum component to a surface of a conductive substrate (first application step), and a step of heat-treating the conductive substrate to which the aqueous precursor solution has been applied at 400 to 800°C in an oxygen-containing atmosphere to form a catalyst layer made of a lithium composite oxide having a rock salt structure on the surface of the conductive substrate (catalyst layer formation step).

[0034] As described above, an intermediate layer may be disposed between the conductive substrate and the catalyst layer as necessary. A method for producing an anode having an intermediate layer thereon includes, before the first coating step, a step of coating the surface of the conductive substrate with an aqueous solution containing lithium ions and nickel ions (second coating step), and a step of heat-treating the conductive substrate to which the aqueous solution has been applied to form a cation-containing electrolyte having the composition formula Li on the surface of the conductive substrate. x Ni 2-x O 2 The method further includes a step of forming an intermediate layer made of a lithium-containing nickel oxide represented by (0.02≦x≦0.5) (an intermediate layer forming step).

[0035] (Pretreatment process) Before forming the intermediate layer and the catalyst layer, the conductive substrate is preferably subjected to a chemical etching treatment in advance in order to remove contaminant particles such as metals and organic matter from the surface. The amount of wear of the conductive substrate due to the chemical etching treatment is 30 g / m 2 More than 400g / m 2 It is preferable that the surface of the conductive substrate is roughened in advance in order to increase the adhesion to the intermediate layer and the catalyst layer. Examples of the roughening method include blasting with powder, etching with an acid soluble in the substrate, and plasma spraying.

[0036] (2nd coating process) In the second application step, an aqueous solution containing lithium ions and nickel ions is applied to the surface of the conductive substrate. The intermediate layer is formed by a so-called pyrolysis method. When forming the intermediate layer by the pyrolysis method, first, an aqueous precursor solution of the intermediate layer is prepared. As the precursor containing a lithium component, known precursors such as lithium nitrate, lithium carbonate, lithium chloride, lithium hydroxide, and lithium carboxylate can be used. As the lithium carboxylate, lithium formate and lithium acetate can be used. As the precursor containing a nickel component, known precursors such as nickel nitrate, nickel carbonate, nickel chloride, and nickel carboxylate can be used. As the nickel carboxylate, nickel formate and nickel acetate can be used. In particular, by using at least one of lithium carboxylate and nickel carboxylate as the precursor, a dense intermediate layer can be formed even when fired at a low temperature as described below, which is particularly preferable.

[0037] (Intermediate layer formation process) In the intermediate layer formation process, the conductive substrate coated with the aqueous solution is heat-treated. x Ni 2-x O 2 An intermediate layer made of a lithium-containing nickel oxide represented by (0.02≦x≦0.5) can be formed on the surface of the conductive substrate. The heat treatment temperature when forming the intermediate layer by the thermal decomposition method can be appropriately set. Considering the decomposition temperature of the precursor and the production cost, the heat treatment temperature is preferably 450 to 600°C, and more preferably 450 to 550°C. For example, the decomposition temperature of lithium nitrate is about 430°C, and the decomposition temperature of nickel acetate is about 373°C. By setting the heat treatment temperature at 450°C or higher, each component can be decomposed more reliably. If the heat treatment temperature is set to more than 600°C, the oxidation of the conductive substrate is likely to proceed, and the electrode resistance increases, which may lead to an increase in voltage loss. The heat treatment time may be appropriately set in consideration of the reaction rate, productivity, oxidation resistance of the intermediate layer surface, etc.

[0038] By appropriately setting the number of times the aqueous solution is applied in the above-mentioned application step, the thickness of the intermediate layer formed can be controlled. The application and drying of the aqueous solution may be repeated for each layer, and the entire structure may be heat-treated after the top layer is formed, or the application and heat treatment (pretreatment) of the aqueous solution may be repeated for each layer, and the entire structure may be heat-treated after the top layer is formed. The temperature of the pretreatment and the temperature of the overall heat treatment may be the same or different. In addition, it is preferable that the time of the pretreatment is shorter than the time of the overall heat treatment.

[0039] (1st coating process) In the first application step, a precursor aqueous solution containing a lithium component, a nickel component, an iron component, and an aluminum component is applied to the surface of the conductive substrate. The catalyst layer is formed by a so-called pyrolysis method. When forming the catalyst layer by the pyrolysis method, first, a precursor aqueous solution of the catalyst layer is prepared. As the precursor containing the lithium component, known precursors such as lithium nitrate, lithium carbonate, lithium chloride, lithium hydroxide, and lithium carboxylate can be used. As the lithium carboxylate, lithium formate and lithium acetate can be used. As the precursor containing the nickel component, known precursors such as nickel nitrate, nickel carbonate, nickel chloride, and nickel carboxylate can be used. As the nickel carboxylate, nickel formate and nickel acetate can be used. In particular, by using at least one of the lithium carboxylate and the nickel carboxylate as the precursor, a dense catalyst layer can be formed even when calcined at a low temperature as described later, which is particularly preferable.

[0040] As the precursor containing an iron component, a known precursor such as iron nitrate, iron carbonate, iron chloride, iron carboxylate, etc. can be used. As the precursor containing an aluminum component, a known precursor such as aluminum nitrate, aluminum carbonate, aluminum chloride, aluminum carboxylate, etc. can be used.

[0041] (Catalyst layer formation process) In the catalyst layer forming step, the conductive substrate coated with the precursor aqueous solution is heat-treated at 400 to 800°C in an oxygen-containing atmosphere. This allows a catalyst layer made of a lithium composite oxide having a rock salt structure to be formed on the surface of the conductive substrate. In consideration of the decomposition temperature of the precursor and production costs, the heat treatment temperature is more preferably 450 to 550°C. By setting the heat treatment temperature to 450°C or higher, each component can be decomposed more reliably. If the heat treatment temperature is too high, the oxidation of the conductive substrate is likely to proceed, and the electrode resistance increases, which may lead to an increase in voltage loss. The heat treatment time may be appropriately set in consideration of the reaction rate, productivity, oxidation resistance of the catalyst layer surface, etc.

[0042] For example, a precursor aqueous solution for forming a catalyst layer can be obtained by dissolving lithium nitrate, nickel nitrate, iron nitrate, and aluminum nitrate in a target composition ratio in a citric acid aqueous solution obtained by dissolving citric acid in ultrapure water. A catalyst (target substance) for alkaline water electrolysis can be obtained by, for example, baking the precursor obtained by evaporating the precursor solution to dryness at 600 to 800°C for 2 to 15 hours.

[0043] The oxygen partial pressure of the oxygen-containing atmosphere when the conductive substrate coated with the precursor aqueous solution is heat-treated is preferably 0.5 atm or more, more preferably 0.9 atm or more. The flow rate of the oxygen-containing gas to be supplied is preferably controlled to 5 mL / min or less, more preferably 2.5 mL / min or less. If the gas flow rate is too high (too fast), Li may be easily volatilized excessively and the generation of oxides may be excessively promoted, so that the composition of the catalyst may easily deviate from the target composition.

[0044] <Use of anodes for alkaline water electrolysis> The anode for alkaline water electrolysis of the present invention can be used as an oxygen generating anode during electrolysis of alkaline water. That is, the anode of the present invention can be used to configure an electrolysis cell such as an alkaline water electrolysis cell. There are no particular limitations on the types or configurations of the negative electrode (cathode) and diaphragm used together with the anode, and cathodes and diaphragms used in conventional alkaline water electrolysis can be used.

[0045] (Cathode) As the cathode, it is preferable to select and use a substrate made of a material that can withstand alkaline water electrolysis and a catalyst with a small cathode overvoltage. As the cathode substrate, a nickel substrate or a nickel substrate coated with an active cathode can be used. The shape of the cathode substrate can be a plate, an expanded mesh, a porous expanded mesh, or the like.

[0046] Cathode materials include porous nickel with a large surface area and Ni-Mo based materials. Other materials include Raney nickel based materials such as Ni-Al, Ni-Zn, and Ni-Co-Zn; sulfide based materials such as Ni-S; Ti 2 Examples of suitable catalysts include hydrogen storage alloy materials such as Ni. As catalysts, those having properties such as low hydrogen overvoltage, high short circuit stability, and high poisoning resistance are preferred. As other suitable catalysts, metals such as platinum, palladium, ruthenium, and iridium, and oxides thereof are preferred.

[0047] (diaphragm) As the diaphragm for electrolysis, asbestos, nonwoven fabric, ion exchange membrane, polymer porous membrane, composite membrane of inorganic substance and organic polymer, etc. can be used. Specifically, an ion-permeable diaphragm can be used in which an organic fiber cloth is embedded in a mixture of a hydrophilic inorganic material such as a calcium phosphate compound or calcium fluoride and an organic binding material such as polysulfone, polypropylene, or polyvinylidene fluoride. Also, an ion-permeable diaphragm can be used in which a stretched organic fiber cloth is embedded in a film-forming mixture of a granular inorganic hydrophilic material such as an oxide or hydroxide of antimony or zirconium and an organic binding agent such as a fluorocarbon polymer, polysulfone, polypropylene, polyvinyl chloride, or polyvinyl butyral.

[0048] By using an alkaline water electrolysis cell including the anode of the present invention as a component, a high-concentration alkaline aqueous solution can be electrolyzed. The alkaline aqueous solution used as the electrolyte is preferably an aqueous solution of an alkali metal hydroxide such as potassium hydroxide (KOH) or sodium hydroxide (NaOH). The concentration of the alkaline aqueous solution is preferably 1.5% by mass or more and 40% by mass or less. In addition, the concentration of the alkaline aqueous solution is preferably 15% by mass or more and 40% by mass or less because it has high electrical conductivity and can reduce power consumption. Furthermore, in consideration of cost, corrosiveness, viscosity, operability, etc., the concentration of the alkaline aqueous solution is preferably 20% by mass or more and 30% by mass or less. EXAMPLES

[0049] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by mass unless otherwise specified.

[0050] <Production of alkaline water electrolysis catalyst (standard material)> (Production Example 1) A precursor solution was prepared by dissolving lithium nitrate, nickel nitrate, iron nitrate, and aluminum nitrate in an aqueous citric acid solution obtained by dissolving citric acid in ultrapure water to obtain a predetermined composition. The prepared precursor aqueous solution was evaporated to dryness to obtain a precursor. The obtained precursor was fired at 800°C for 15 hours to obtain a powdered target material. A portion of the obtained standard material was dissolved in acid to obtain a solution, and the composition was analyzed by inductively coupled plasma (ICP) atomic emission spectrometry. As a result, the composition of the obtained target material (catalyst) was "Li(Ni 0.8 Fe 0.2 ) 0.9 Al 0.1 O 2 Figure 4 shows the Li(Ni 0.8 Fe 0.2 ) 0.9 Al 0.1 O 2 This X-ray diffraction pattern was subjected to Rietveld analysis to obtain the diffraction peak intensity I (104) Diffraction peak intensity I of the 003 plane (003) The ratio (I (003) / I (104) ) was confirmed to be 1.76.

[0051] 5 mg of the target substance (catalyst) and 45 μL of 5% Nafion solution were added to 2 mL of ethanol and shaken for 1 hour using ultrasonic waves to prepare a catalyst ink. 2 ) was applied to an RDE (GC) electrode with a diameter of 5 mm. Then, using a PFA three-electrode cell with the configuration shown below, electrolysis was performed at 30 ± 1 °C. Note that cyclic voltammetry (0.5-1.6 V vs. RHE, 200 mV / s, 100 cycles) was performed as a pretreatment, and the current was measured at a potential of 1.1-1.7 V and a sweep rate of 5 mV / s while rotating the electrode at 1,600 rpm. As a result, the current value at 1.6 V was 20 mA / cm 2 The results of cyclic voltammetry (cyclic voltammogram) are shown in FIG. [Three-electrode cell]: Working electrode: Ni wire etched in boiling hydrochloric acid for 6 minutes Reference electrode: Reversible hydrogen electrode (RHE) Counter electrode: Pt coil ·Electrolyte: 0.1M KOH aqueous solution 250mL

[0052] (Production Example 2) The composition of the precursor aqueous solution was adjusted in the same manner as in the above-mentioned Production Example 1, except that the composition of the precursor aqueous solution was adjusted to "Li(Ni 0.8 Fe 0.2 ) 0.95 Al 0.05 O 2 We prepared a target substance (catalyst) represented by the formula "I". (003) / I (104) It was confirmed that the value of was 1.76. Furthermore, a three-electrode cell was prepared in the same manner as in Production Example 1 above, and electrolysis was carried out. As a result, the current value at 1.6 V was 7 mA / cm 2 The results of cyclic voltammetry (cyclic voltammogram) are shown in FIG.

[0053] (Comparative Manufacturing Example 1) The composition of the precursor aqueous solution was adjusted in the same manner as in the above-mentioned Production Example 1, except that the composition of the precursor aqueous solution was adjusted to "LiNi 0.8 Fe 0.2 O 2 We prepared a target substance (catalyst) represented by the formula "I". (003) / I (104) It was confirmed that the value of was within the range of 0.1 to 1.9. Furthermore, a three-electrode cell was prepared in the same manner as in Production Example 1 above, and electrolysis was carried out. As a result, the current value at 1.6 V was 5 mA / cm 2 The results of cyclic voltammetry (cyclic voltammogram) are shown in FIG.

[0054] (Comparative Manufacturing Example 2) The composition of the precursor aqueous solution was adjusted in the same manner as in the above-mentioned Production Example 1, except that the composition of the precursor aqueous solution was adjusted to "LiNi 0.8 Al 0.2 O 2We prepared a target substance (catalyst) represented by the formula "I". (003) / I (104) It was confirmed that the value of was within the range of 0.1 to 1.9. Furthermore, a three-electrode cell was prepared in the same manner as in Production Example 1 above, and electrolysis was carried out. As a result, the current value at 1.6 V was 5 mA / cm 2 It was.

[0055] <Anode manufacturing> Example 1 As the anode substrate, a nickel expanded mesh (10 cm x 10 cm, LW x 3.7 SW x 0.9 ST x 0.8 T) was prepared, which was immersed in 17.5% hydrochloric acid heated to near the boiling point for 6 minutes and chemically etched. This expanded mesh was blasted (0.3 MPa) with 60 mesh alumina particles, and then immersed in 20% hydrochloric acid heated to near the boiling point for 6 minutes and chemically etched. An aqueous solution containing a component that will be a precursor of lithium-containing nickel oxide was applied to the surface of the anode substrate after the chemical etching treatment with a brush, and then dried at 80 ° C for 15 minutes. Next, it was heat-treated at 600 ° C for 15 minutes in an oxygen atmosphere. The process from application of the aqueous solution to heat treatment was repeated 20 times to form an intermediate layer (composition: Li 0.5 Ni 1.5 O 2 ) was formed to give an intermediate.

[0056] A precursor aqueous solution was obtained by dissolving lithium nitrate, nickel nitrate, iron nitrate, and aluminum nitrate in a citric acid aqueous solution to a predetermined composition. The obtained precursor aqueous solution was applied with a brush to the surface of the intermediate layer of the intermediate obtained above, and then dried at 80°C for 15 minutes. Next, the intermediate layer was heat-treated at 600°C for 15 minutes in a pure oxygen atmosphere. The process from application of the precursor aqueous solution to heat treatment was repeated 20 times to form a catalyst layer (composition: Li(Ni 0.8 Fe 0.2 ) 0.9 Al 0.1 O 2 The anode was obtained by forming the catalyst layer I (003) / I (104) The value was confirmed to be 1.76.

[0057] A small zero-gap electrolysis cell using a neutral diaphragm was fabricated using the obtained anode, a diaphragm (trade name "Zirfon", manufactured by AGFA), and an active cathode with a catalytic layer made of Ru and Pr oxide. The electrode area was 19 cm. 2 An electrolyte (25% KOH aqueous solution) was supplied to the anode and cathode chambers constituting the electrolytic cell, and the current density was 6 kA / m 2 The electrolysis was carried out for 6 hours at 1000 V for each. The overvoltage at this time was 250 mV. Next, the anode and cathode were short-circuited (0 kA / m 2 ) and shut down for 15 hours. A shutdown test was conducted, with the operation from electrolysis to shutdown being one cycle. As a result, it was confirmed that the voltage was kept stable in 20 shutdown tests.

[0058] Comparative Example 1 The composition of the catalyst layer is "LiNi 0.8 Fe 0.2 O 2 An anode was produced in the same manner as in the above-mentioned Example 1, except that "." Furthermore, when electrolysis was carried out in the same manner as in the above-mentioned Example 1, the overvoltage was 350 mV. [Industrial Applicability]

[0059] The anode for alkaline water electrolysis of the present invention is suitable, for example, as an anode for alkaline water electrolysis constituting electrolysis equipment or the like powered by electric power with large output fluctuations, such as renewable energy. [Explanation of symbols]

[0060] 2: Conductive substrate 4: Middle layer 6: Catalyst layer 10: Anode for alkaline water electrolysis

Claims

1. A conductive substrate, at least the surface of which is made of nickel or a nickel-based alloy; a catalyst layer made of a lithium composite oxide having a rock salt structure, the catalyst layer being disposed on a surface of the conductive substrate; The anode for alkaline water electrolysis, wherein the lithium composite oxide contains lithium (Li), nickel (Ni), iron (Fe), and aluminum (Al), and the atomic ratio of Li / Ni / Fe / Al / O is 1 / (0.72 to 0.76) / (0.18 to 0.19) / (0.05 to 0.1) / 2 (with the proviso that the sum of the atomic ratios of Ni, Fe, and Al is 1).

2. The diffraction peak intensity I of the 104 plane of the catalyst layer measured by X-ray diffraction (104) Diffraction peak intensity I of the 003 plane (003) The ratio (I (003) / I (104) 2. The anode for alkaline water electrolysis according to claim 1, wherein R 2 is 0.1 to 1.

9.

3. A composition formula Li x Ni 2-x O 2 The anode for alkaline water electrolysis according to claim 1 or 2, further comprising an intermediate layer made of a lithium-containing nickel oxide represented by (0.02≦x≦0.5).

4. A step of applying an aqueous precursor solution containing a lithium component, a nickel component, an iron component, and an aluminum component to a surface of a conductive substrate, at least the surface of which is made of nickel or a nickel-based alloy; and a step of heat-treating the conductive base coated with the aqueous precursor solution at 400 to 800° C. in an oxygen-containing atmosphere to form a catalyst layer made of a lithium composite oxide having a rock salt structure on the surface of the conductive base material, The lithium composite oxide contains lithium (Li), nickel (Ni), iron (Fe), and aluminum (Al), and an atomic ratio of Li / Ni / Fe / Al / O is 1 / (0.72-0.76) / (0.18-0.19) / (0.05-0.1) / 2 (with the proviso that the sum of the atomic ratios of Ni, Fe, and Al is 1).

5. The method for producing an anode for alkaline water electrolysis according to claim 4, wherein the conductive substrate coated with the aqueous precursor solution is heat-treated in an oxygen-containing atmosphere having an oxygen partial pressure of 0.5 atmospheres or more.

Citation Information

Patent Citations

  • Three-dimension carbon cloth / nickel iron layer shaped hydroxide nanosheet composite material and application thereof

    CN108107101A

  • Nickel-iron bi-metal hydroxide@ cerium dioxide heterostructure nanosheet material and preparation method and application thereof

    CN108447703A

  • Fabrication method and application of ampicillin sensor

    CN109254049A

  • Foam nickel@cobalt molybdenum phosphide / nickel iron double hydroxide electrode, preparation method and application thereof

    CN110344078A

  • Anode for alkali water electrolysis

    JP2015086420A